Sex Education to Prevalence of Sexual Harassment in Children with Autism - Ayuningtyas, Fitria; Genilo, Jude William R; Hakim, Luqman; Misbah, Nuril A; Sutowo, Irpan Ripai (LP2M INSURI Ponorogo, 2023)
Children with autism, like children in general, also have experienced sexual development. The unique condition of children with autism (ASD) sometimes makes them engage in inappropriate sexual behavior and become vulnerable to sexual violence. Therefore, sexual education for children with autism is crucial and urgent. A team conducted this community service in January 2020 to provide social stories and PECS (Picture Exchange Communication System) as alternative teaching materials for sex education to children with autism at Rumah Autis Depok. The methods used were pre-observation, unstructured discussion and interview, implementation preparation, implementation, and monitoring. They quickly understood the message intended from PECS and social stories. The sex education materials showed differences in male and female bodies, sexes, and reproductive functions. This material is the starting material in sex education. Continuity using the same learning tools, namely social stories and PECS, is therefore required. Our monitoring process shows that Rumah Autis Depok continues to use social stories and PECS in their sex education lessons